2021
DOI: 10.1016/j.nrl.2021.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Safety of anti-CGRP monoclonal antibodies in patients with migraine during the COVID-19 pandemic: Present and future implications

Abstract: Antecedentes y objetivo: El péptido relacionado con el gen de la calcitonina (CGRP, por sus siglas en inglés), es un neuropéptido involucrado en la fisiopatología de la migraña que también es conocido por participar en la función del sistema respiratorio y en algunas enfermedades inmunológicas como la sepsis. Hemos analizado el impacto del uso de los antagonistas de CGRP en pacientes con migraña durante la pandemia de COVID-19, causada por el coronavirus SARS-CoV-2. Métodos: Estudio transversal mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 8 publications
0
14
0
1
Order By: Relevance
“…The complex CGRP physiology accounts for the observed appropriate or detrimental effects of CGRP or CGRP receptor antagonist drugs in different clinical conditions [ 6 , 26 ]. To date, monoclonal antibodies targeting CGRP are available to treat migraines [ 43 ] and are safe in clinical practice in terms of COVID-19 infection susceptibility [ 44 , 45 ]. Moreover, it has been hypothesized that in COVID-19, a crosstalk between the lungs and the neuro–immune axis could take place, sustaining the development of a clinical trial aimed to investigate the effectiveness of vazegepant, an anti-CGRP molecule initially developed to treat migraines, in COVID-19 management [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The complex CGRP physiology accounts for the observed appropriate or detrimental effects of CGRP or CGRP receptor antagonist drugs in different clinical conditions [ 6 , 26 ]. To date, monoclonal antibodies targeting CGRP are available to treat migraines [ 43 ] and are safe in clinical practice in terms of COVID-19 infection susceptibility [ 44 , 45 ]. Moreover, it has been hypothesized that in COVID-19, a crosstalk between the lungs and the neuro–immune axis could take place, sustaining the development of a clinical trial aimed to investigate the effectiveness of vazegepant, an anti-CGRP molecule initially developed to treat migraines, in COVID-19 management [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies targeting CGRP (CGRP-mAbs) have been found to be safe in clinical practice in terms of COVID-19 infection susceptibility and hospitalization/symptoms [ 4 ]. No data are currently available regarding CGRP-mAbs and COVID-19 vaccines.…”
Section: Dear Sirsmentioning
confidence: 99%
“…Therefore, they can still represent a therapeutic option in headache prevention. Second, as CGRP may promote or protect from inflammation, the safety of CGRP antagonism during the pandemic has been studied comparing migraine patients with and without anti-CGRP monoclonal antibodies [71]. Results showed that they seem to be safe as the number of COVID-19 cases and severity were similar between groups.…”
Section: Treatmentmentioning
confidence: 99%